The key players of inflammasomes and pyroptosis in sepsis-induced pathogenesis and organ dysfunction - Zhu, Lujian; Hu, Minli; Xu, Haoming; Xu, Hanglu; Ren, Binbin; Xu, Ruiyan; Guo, Maodong; Chen, Haijun; Zhang, Dehe; Fang, Hao (Frontiers in Pharmacology, 2025)
Pyroptosis is an inflammatory form of cell death involving caspase-1 or caspase-4/5/11, initiated by inflammasomes or cytoplasmic endotoxins as part of the immune defense. It is specifically characterized by Gasdermin-mediated pore formation leading to cell lysis, pyroptosis also entails the release of pro-inflammatory cytokines. As a natural mechanism of the immune system, it activates in response to harmful stimuli to eliminate threats and facilitate tissue repair. However, excessive pyroptosis can lead to detrimental outcomes, such as infectious shock, multiple organ dysfunction syndrome (MODS), and increased susceptibility to secondary infections. Sepsis, an unchecked immune response to infection, remains a leading cause of MODS and death among critically ill patients. The pathogenesis of sepsis is complex and multifaceted, involving innate inflammation that kills infected cells and releases pro-inflammatory cytokines. Recent research has increasingly explored the link between pyroptosis and sepsis, focusing on its mechanisms, roles, and potential therapeutic targets. There has been significant advancement in understanding pyroptosis, highlighting its vital role in the development of sepsis. This review delves into the molecular and pathophysiological roles of inflammasomes and pyroptosis in sepsis, with a particular emphasis on the impact on specific organs such as the heart, lungs, liver, kidney and brain, aiming to identify new diagnostic markers and therapeutic targets for sepsis management.